Resilience reconciled - Allen, Craig R.; Angeler, David G.; Chaffin, Brian C.; Twidwell, Dirac; Garmestani, Ahjond (2019)
Resilience scholarship continues to inspire opaque discourse and competing frameworks often inconsistent with the complexity inherent in social–ecological systems. We contend that competing conceptualizations of resilience are reconcilable, and that the core theory is useful for navigating sustainability challenges.